2018
DOI: 10.1111/anec.12618
|View full text |Cite
|
Sign up to set email alerts
|

Could fragmented QRS predict mortality in aortic stenosis patients after transcatheter aortic valve replacement?

Abstract: Aortic stenosis has become a more common health problem as the population ages (Thaden, Nkomo, & Enriquez-Sarano, 2014).Transcatheter aortic valve replacement (TAVR) has widely been used for calcific aortic stenosis in patients with high surgery risk (Perrin, Frei, & Noble, 2018). Thus, the patients who are candidates for TAVR possess more risk factors and comorbidities. In advanced aortic stenosis, chronic pressure overload causes myocyte cell death and myocardial fibrosis, resulting in the transition from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Rattanawong et al showed that fQRS could be an important tool for risk assessment in patients with Brugada syndrome and hypertrophic cardiomyopathy (HCM; Rattanawong, Riangwiwat, Kanitsoraphan, et al, 2018;Rattanawong, Riangwiwat, Prasitlumkum, et al, 2018). Gulsen et al showed that fragmented QRS could predict mortality in aortic stenosis patients after transcatheter aortic valve replacement (TAVR) procedure (Gulsen et al, 2019). Kanitsoraphan et al showed that baseline fQRS is associated with increased all-cause mortality in patients with HF reduced LVEF (Kanitsoraphan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rattanawong et al showed that fQRS could be an important tool for risk assessment in patients with Brugada syndrome and hypertrophic cardiomyopathy (HCM; Rattanawong, Riangwiwat, Kanitsoraphan, et al, 2018;Rattanawong, Riangwiwat, Prasitlumkum, et al, 2018). Gulsen et al showed that fragmented QRS could predict mortality in aortic stenosis patients after transcatheter aortic valve replacement (TAVR) procedure (Gulsen et al, 2019). Kanitsoraphan et al showed that baseline fQRS is associated with increased all-cause mortality in patients with HF reduced LVEF (Kanitsoraphan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Имеются данные о связи блокад ножек пучка Гиса на исходной ЭКГ с более высоким уровнем сердечно-сосудистой и общей смертности при 5-летнем наблюдении у больных с тяжелым симптомным АС, перенесших протезирование аортального клапана [10]. Также имеются работы, демонстрирующие связь фрагментации комплекса QRS на исходной ЭКГ с более высоким уровнем госпитальной и долгосрочной смертности у больных, перенесших ТИАК [11,12]. В изученной нами группе больных внутрижелудочковые блокады и фрагментация QRS в грудных отведениях чаще встречались у больных с ЛГ.…”
Section: Discussionunclassified